196k views
0 votes
Solve this system by elimination : -5x + 3z =8 x- 4y = 7 5y - 4z = -14 find the x , y and z using elimination

User Fabianvf
by
4.7k points

1 Answer

5 votes

Answer

• x = –1

• y = –2

• z = 1

Step-by-step explanation

Given the system:


\begin{gathered} -5x+3z=8\text{, equation 1} \\ 5y-4z=-14,\text{ equation 2} \\ x-4y=7,\text{ equation 3} \end{gathered}

We have to divide equation 1 over 5 and add it to equation 2:


\begin{gathered} -(5x)+0y+3z=8 \\ x-4y+0z=7 \\ 0x+5y-4z=-14 \end{gathered}
\begin{gathered} (-(5x)+0y+3z=8)/(5) \\ x-4y+0z=7 \\ 0x+5y-4z=-14 \end{gathered}
\begin{gathered} -x+0y+(3)/(5)z=(8)/(5) \\ x-4y+0z=7 \\ 0x+5y-4z=-14 \end{gathered}

Now, we have to add 1/5(equation 1) to equation 2:


\begin{gathered} -x+0y+(3)/(5)z=(8)/(5) \\ x-4y+0z=7 \\ --------- \\ 0x-4y+(3)/(5)z=(43)/(5) \end{gathered}

Next, we multiply the equation 2 obtained previously times 5:


\begin{gathered} (0x-4y+(3)/(5)z=(43)/(5))\cdot5 \\ -20y+3z=43 \end{gathered}

Then, we divide equation 2 over 4:


\begin{gathered} (-20y+3z=43)/(4) \\ -5y+(3)/(4)z=(43)/(4) \end{gathered}

We add it to equation 3:


\begin{gathered} -5y+(3)/(4)z=(43)/(4) \\ 5y-4z=-14 \\ ------- \\ 0y-(13)/(4)z=-(13)/(4) \end{gathered}

Then, we are left with:


\begin{equation*} -(13)/(4)z=-(13)/(4) \end{equation*}

Simplifying:


-13z=-13
z=(-13)/(-13)=1
z=1

Now that we have the value of z (z = 1), we can replace it in the modified equation 2 and solve for y:


-20y+3z=43
-20y+3(1)=43
-20y+3=43
-20y=43-3
-20y=40
y=(40)/(-20)
y=-2

Finally, calculating the value of x with any of the equations (as we already have the other two values):


x-4(-2)=7
x+8=7
x=7-8
x=-1

User Kamal Paliwal
by
5.9k points